PortFindr: A Novel, More Accurate, and Precise Device for Locating Tissue Expander Ports. Issue 2 (May 2021) - McCulloch, Ian L.; Rokosz, Jennifer; Chambers, Justin; McClellan, W. Thomas
Two-stage breast reconstruction is the most common method of reconstructive modality following mastectomy and requires serial saline infusions into temporary tissue expanders through subcutaneous ports. Historically, these ports were located using a small magnet attached to a string or support structure. Magnetic force decreases exponentially as tissue thickness or fluid accumulation creates more distance between the TE port and skin. We developed a prototype handheld electronic device, the PortFindr, which more accurately and precisely locates the centre of subcutaneous ports. This device may lead to more confident localization of ports, less inadvertent puncture of tissue expanders, and thus less complications during infusions.